Posttraumatic stress disorder and risk factors in parents of children with a cancer diagnosis - (:unkn) unknown (TAYLOR & FRANCIS INC, 2008)
The purpose of this study was to determine the prevalence of posttraumatic stress disorder (PTSD) in parents of children with cancer. Five questionnaires were administered to 104 parents, including a sociodemographic questionnaire, a traumatic events check list, the Structured Clinical Interview for DSM-IV PTSD and Major Depressive Disorder modules, and the self-rating instrument General Health Questionnaire-12. The prevalence of PTSD was 34.6%. The statistically significant tendency to develop PTSD were found in the female gender, better educational status, death of a loved one, previous history of psychiatric disorder, having a child with poorer prognosis, and the presence of radiotherapy in child's treatment. The vulnerable parents must receive psychosocial support.
Keywords: parents; pediatric cancer; posttraumatic stress disorder; PEDIATRIC CANCER; CHILDHOOD-CANCER; EARTHQUAKE SURVIVORS; TRAUMATIC STRESS; SOCIAL SUPPORT; SYMPTOMS; MOTHERS; PTSD; SYMPTOMATOLOGY; FAMILIES